TINDAK TUTUR ILOKUSI TEKS POSTER PERBAIKAN TROTOAR JALAN UTAMA KOTA PONTIANAK: KAJIAN TEORI SEARLE - Wahyu Damayanti (tuahtalino, 2021)
Communication through posters is representative in conveying information that is included in the types of speech acts. These posters are  found along the main road in Pontianak City, Some posters are closely related to the repair of sidewalks for pedestrians. The purpose of this research is to describe the types and forms of illocutionary speech acts of the poster text of the pavement improvement of the main road in Pontianak City based on the study of Searle's theory. Qualitative descriptive research method. The research data is speech acts and road repair posters along the main road in Pontianak city. The researcher found the source of written speec data on posters made by jasa marga in the city of Pontianak. Data collection techniques are documentation and notes. The documentation technique is done by taking notes and taking photos of the posters along the repaired sidewalks. The results showed that illocutionary speech acts in the poster text consisted of five types of illocutionary speech acts, including Assertive, in the form of stating, claiming and suggesting, Directivein the form of recommending, giving messages, ordering, advising and recommending, Expressive, in the form of apologizing, Commissive, in the form of threats,  and Declaration, in the form of punishing.